SYNERGY OF TRANSFORMATIONAL LEADERSHIP STYLE AND COMPENSATORY JUSTICE IN BUILDING JOB SATISFACTIO N OF STATE ISLAMIC SENIOR HIGH SCHOOL TEACHERS IN PEKANBARU CITY - Prayuni, Ary; Rafida, Tien; Rifa’i, Muhammad; Nisoh, Anan (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
This study aims to analyze the influence of transformational leadership style and compensation fairness on job satisfaction of State Islamic Senior High School teachers in Pekanbaru City. Transformational leadership style is believed to be able to create positive changes by providing inspiration, individual attention, and intellectual encouragement for teachers to develop their potential and performance. Meanwhile, compensation fairness reflects the suitability between financial and non-financial rewards received by teachers with the contributions they make to the institution. This study uses a quantitative approach with a survey method. The results show that transformational leadership style has a positive and significant effect on teacher job satisfaction with an influence coefficient of 0.282 and a calculated t value of 4.035 > t table 1.653. Similarly, compensation has a positive and significant effect on teacher job satisfaction with an influence coefficient of 0.329 and a calculated t value of 5.317 > t table 1.653. These findings confirm that the more effective the implementation of transformational leadership style and the more fair the compensation system implemented, the higher the level of teacher job satisfaction. The implications of this research show the importance of strengthening the leadership capacity of madrasah principals that is inspirational, humanistic, and empowerment-oriented, as well as the implementation of a transparent and proportional compensation system to improve the welfare, motivation, and performance of teachers in the State Madrasah Aliyah environment of Pekanbaru City.